Second order duality for minimax programming - Liu J.C. (Utilitas Mathematica, 1999)
We apply the optimality conditions of minimax programming to formulate general second order Mond-Weir dual to the minimax programming involving second order pseudo B-invex and second order quasi B-invex functions, We also establish weak, strong, and strict converse duality theorems.